2021
DOI: 10.1111/jnu.12667
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Using Multiple Mobile Health Devices to Support Self‐Management Among Adults With Type 2 Diabetes: A Qualitative Descriptive Study

Abstract: This study identified facilitators and barriers pertaining to the use of multiple mobile health (mHealth) devices (Fitbit Alta® fitness tracker, iHealth® glucometer, BodyTrace® scale) that support self-management behaviors in individuals with type 2 diabetes mellitus (T2DM). Design: This qualitative descriptive study presents study participants' perceptions of using multiple mobile devices to support T2DM self-management. Additionally, this study assessed whether participants found visualizations, generated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 29 publications
4
10
0
3
Order By: Relevance
“…In this study, the participants' described the importance of having a step goal to strive for. That is also shown in other qualitative studies reporting experiences from individuals with OA, arthritis, and type 2 diabetes (33,39,53).…”
Section: Discussionsupporting
confidence: 71%
“…In this study, the participants' described the importance of having a step goal to strive for. That is also shown in other qualitative studies reporting experiences from individuals with OA, arthritis, and type 2 diabetes (33,39,53).…”
Section: Discussionsupporting
confidence: 71%
“…Correspondingly, a qualitative study reported that patients with OA or inflammatory arthritis described that the WAT reinforced their motivation and helped them to reach their activity goal [36]. The importance of having a step goal to strive for is also shown in other qualitative studies reporting experiences from individuals with OA, arthritis, and type 2 diabetes [36,42,57]. The participants in this study also experienced that the WAT made them aware of how many steps per day that was optimal for them to avoid worsening of pain.…”
Section: Discussionmentioning
confidence: 87%
“… RCT Damayanti et al 47 Older adults, average age 61, 50% male, SMS Improved diet, exercise, blood-glucose testing, and foot care Improved blood-glucose testing, and foot care Quasi-experimental Fu et al 48 Older adults mHealth apps and SMS Improved self-management behaviors Improved self-management behaviors Qualitative Jia et al 49 Older adults mHealth enabled hierarchical diabetes management Overall improvement of HbA1C, but no statistically significant differences in weight changes. Improved HbA1C RCT Lee et al 50 Older adults mHealth apps and coaching Improved self-management behaviors Improved HbA1C RCT Lewinski et al 51 Older adults mHealth No control group Not reported Qualitative Li et al 52 Older adults mHealth app and wearable sensor Intervention group showed larger increase in cardiopulmonary endurance, larger decrease in body fat percentage Increase in cardiopulmonary endurance, decrease in body fat percentage RCT Montero et al 53 Older adults, average age 56.1, 81% Black, 62% female Cellular remote monitoring, Biotel system dashboard + telemedicine visits Statistically significant difference in HbA1C levels between groups as well as user confidence in self-management Improvement in HbA1C True experiment Prabhu et al …”
Section: Resultsmentioning
confidence: 99%
“…This theme appeared 26/31 (84%) of the occurrences. 29 , 32 , 33 , 35–39 , 41–58 Four other observations were identified, but they could not be fit into themes: “Activity on app increased for those recently diagnosed with diabetes”, “users were dissatisfied with usefulness”, “travel savings were greatly appreciated because the mHealth app prevented them from driving into the clinic”, and “users requested larger fonts and simplified data visualizations.” 30 , 34 , 40 , 52 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation